AN ANALYSIS OF DIFFERENTIATED LEARNING IN DEVELOPING ENGLISH READING SKILLS - Mambarasi Nehe, Berita; Shuhaida Abdull Rahman, Zainatul; Suherman; Cahyono, Habib; Aryadi, Dedi; Nisa, Baiatun; Hidayat Suharto, Taufik (Department of English Education, Universitas Panca Sakti Bekasi, 2024)
The purpose of this study is to analyze the differentiated learning in developing English reading skills among high school students. Differentiated learning provides the diverse learning needs of students by providing adjusted learning experiences. This qualitative research was conducted in a high school in Lebak Regency, involving in-depth interviews. Participants included 10 English teachers who were selected through purposive sampling. Data were collected through semi-structured interviews to explore perceptions and experiences. The results revealed that differentiated learning positively provided by teachers on 5 aspects, they are teaching materials, various teaching method, flexibility assignment, students grouping, and different assessment. Ten Teachers really understand how to treat various students in the classroom using varied learning strategies, such as tiered assignments and flexible grouping, helped meet individual student needs and improved engagement. The discussion highlights the effectiveness of differentiated learning in creating a supportive learning environment that addresses diverse learning styles and needs. It emphasizes the importance of teacher training and resource availability for successful implementation. The study concludes that differentiated learning is a valuable method for enhancing reading skills in high school students, promoting better educational outcomes and fostering inclusivity